2019
DOI: 10.1186/s12879-019-3738-4
|View full text |Cite
|
Sign up to set email alerts
|

Test and Treat TB: a pilot trial of GeneXpert MTB/RIF screening on a mobile HIV testing unit in South Africa

Abstract: BackgroundCommunity-based GeneXpert MTB/RIF testing may increase detection of prevalent TB in the community and improve rates of TB treatment completion.MethodsWe conducted a pilot randomized trial to evaluate the impact of GeneXpert screening on a mobile HIV testing unit. Adults (≥18y) underwent rapid HIV testing and TB symptom screening and were randomized to usual mobile unit care (providing sputum on the mobile unit sent out for GeneXpert testing) or the “Test & Treat TB” intervention with immediate GeneXp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…An alternative approach would be to deploy mobile laboratories with high-capacity systems capable of performing many tests simultaneously and equipped with appropriate biocontainment equipment. Such mobile laboratory capacity has already been deployed to find active cases of tuberculosis among at-risk populations in South Africa (18). Similar mobile laboratory capacity could potentially be made available in the current outbreak and potential future seasonal outbreaks and could be used to find active cases in nursing homes and for testing other less ambulatory populations, with results available on site and in an actionable time frame.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach would be to deploy mobile laboratories with high-capacity systems capable of performing many tests simultaneously and equipped with appropriate biocontainment equipment. Such mobile laboratory capacity has already been deployed to find active cases of tuberculosis among at-risk populations in South Africa (18). Similar mobile laboratory capacity could potentially be made available in the current outbreak and potential future seasonal outbreaks and could be used to find active cases in nursing homes and for testing other less ambulatory populations, with results available on site and in an actionable time frame.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of GeneXpert MTB/RIF has greatly improved TB case finding; however, this technology has been mainly relegated to laboratories and healthcare facilities [39,40]. Recent intensified case finding studies have explored the feasibility and effectiveness of integrating GeneXpert platforms into community‐based mobile HIV testing vans [41,42]. Given the need to improve active case finding and linkage to care amongst household contacts of TB patients, we adapted a GeneXpert single module (GX‐I) instrument for portability and use during household contact tracing investigations [43].…”
Section: Introductionmentioning
confidence: 99%
“…The higher cost of mobile testing should be weighed against the impact of earlier diagnosis, improved coverage, same-day treatment and care, as well as reduced loss to follow-up. 17 , 28 , 29 , 30 , 31 Mobile testing as an extension of laboratory testing could also see its higher costs offset by high volume laboratory testing, as bulk testing is still reserved for the laboratory service. The findings of this study confirmed that mobile testing is 3.2 times more expensive than conventional laboratory testing on the same GeneXpert testing platform.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that mobile testing is feasible, improves access to diagnostics, and may improve linkage to care and decrease time to treatment. 14 , 15 , 16 , 17 A local study has reported that linkage to tuberculosis treatment was not associated with either sex or service type (mobile versus stand-alone), but older patients were less likely to be linked to tuberculosis treatment. 15 Mobile testing for HIV, tuberculosis and, more recently, severe acute respiratory syndrome coronavirus 2 can bring diagnostics to where it is needed in high-burden or outbreak communities.…”
Section: Introductionmentioning
confidence: 99%